From savage to Negro : anthropology and the construction of race, 1896-1954 - Baker, Lee D., 1966- (University of California Press, 1998)
Lee D. Baker explores what racial categories mean to the American public and how these meanings are reinforced by anthropology, popular culture, and the law. Focusing on the period between two landmark Supreme Court decisions-Plessy v. Ferguson (the so-called "separate but equal" doctrine established in 1896) and Brown v. Board of Education (the public school desegregation decision of 1954)-Baker shows how racial categories change over time. Baker paints a vivid picture of the relationships between specific African American and white scholars, who orchestrated a paradigm shift within the social